2007
DOI: 10.1111/j.1559-1816.2007.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Attachment and Met Expectations as Predictors of Retirement Adjustment of Naval Officers1

Abstract: Attachment to one's former occupation and met expectations regarding retirement were proposed as predictors of the adjustment of military retirees. While results suggested that occupational attachment had a minimal impact, the extent to which expectations of civilian work, financial, and family aspects of life were met emerged as significant predictors of satisfaction and adjustment after military retirement. These findings suggest that the characteristics of the post‐retirement environment, and expectations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Given a specific structural situation, individuals might differ in the way they evaluate the consequences of retirement (Henkens, 1999). Prior research has shown that preretirement expectations about life in retirement are important predictors of retirement decisions (Henkens, 1999) and adjustment to retirement (Taylor, Shultz, Spiegel, Morrison, & Greene, 2007;Van Solinge & Henkens, 2008). This study will examine whether they also play a role for explaining differences in terms of postretirement work role residuals.…”
Section: Introductionmentioning
confidence: 99%
“…Given a specific structural situation, individuals might differ in the way they evaluate the consequences of retirement (Henkens, 1999). Prior research has shown that preretirement expectations about life in retirement are important predictors of retirement decisions (Henkens, 1999) and adjustment to retirement (Taylor, Shultz, Spiegel, Morrison, & Greene, 2007;Van Solinge & Henkens, 2008). This study will examine whether they also play a role for explaining differences in terms of postretirement work role residuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the areas that is still unclear is how older workers' views on their jobs impact on their expectations of retirement (Flynn and McNair, 2008). Therefore, recent work in the retirement literature has concentrated on the importance of psychosocial variables in predicting attitudes towards retirement decisions (Crego et al, 2008, Taylor et al, 2007, Wong and Earl, 2009, Zappala et al, 2008. Psychosocial variables relate to the meaning that work plays in an individual's life (for example, their commitment to the organisation, and to work itself) but also their attitudes and expectations of retirement.…”
Section: Normal Retirement Age 1 Introductionmentioning
confidence: 99%
“…These individuals may well have been pulled into retirement rather than pushed, which increased their satisfaction. Conversely, other studies found no effect for occupation (Calasanti 1996;Taylor et al 2007). Though these results do not reference specifically union membership or at University of Hawaii at Manoa Library on June 25, 2015 ilr.sagepub.com Downloaded from the nature of the types of tasks conducted on the pre-retirement job, they do suggest that prior work may influence later retirement satisfaction.…”
Section: Determinants Of Retirement Satisfaction: Prior Researchmentioning
confidence: 90%